Development of an Interprofessional Handoff Assessment for Doctor of Physical Therapy Students. Issue 4 (2nd June 2022) - Ronnebaum, Julie; Jie, Chunfa; Salazar, Kristina
Abstract : Background and Purpose: Handoff communication, especially interprofessional (IPE) handoff communication, has been shown to make up a large portion of communication errors in health care. There is variability in the way professionals are trained and deliver the pertinent patient information in handoffs, which, causes confusion, makes recall difficult, and increases the incidence of medical errors. Thus, this study aimed at assessing IPE handoffs for individuals who are trained in SBAR (Situation, Background, Assessment, and Recommendation) method of IPE communication developed by TEAM STEPPS®. Method: To assess IPE handoffs for those who are trained with the SBAR method, an existing tool was modified to make it more explicit to IPE handoff communication using descriptors from SBAR. Reliability and internal consistency were evaluated using videos of IPE handoffs of doctor of physical therapy (DPT) students. Results: Spearman rank coefficients for the revised assessment domains ranged from 0.56 to 0.86, indicating a strong correlation. The communication and content domains had the highest level of correlation. The interrater reliability of the 5 raters was 0.85, indicating high reliability. Discussion and Conclusion: This assessment proved to be simple and reliable to measure IPE handoff communication skills during emergent situations between DPT students and standardized nurses. Thus, this assessment can be used to assess interprofessional handoffs, develop competencies improved teamwork, and reduce medical errors.